Analisis Prinsip Kerja Sama dalam Acara Komedi Extravaganza - Faizal Arvianto (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2019)
In language studies, there is a study of the use of language which is intended as an effort to guide conversation participants to be able to carry out cooperative conversations, namely pragmatic studies, especially in the part of the principle of cooperation. Grice divides four maxims which establish the principle of cooperation. The four maxims are the maxims of Quality, quantity, relationships, and ways. The object of the study in this analysis is the comedy Extravaganza program "Love in the Restaurant" which aired on Trans TV. From the results of the analysis using cooperative principles, conversational data were obtained which showed the existence of quality maxims (Maxime der Qualität) in 4 conversations, 3 conversations violating maxims and 1 not violating maxims. Whereas for the maximum quantity (Maxime der Quantität) there are 12 conversations, 2 of which violate maxims and 10 do not violate maxims. Furthermore, for the maximal relevance (Maxime der Relevanz) data obtained as many as 3 conversations and all are declared relevant / not violating the maxim. Whereas for the maximal means (Maxime der Modalität) there were 2 conversations, 1 conversation showed a violation of maxims and the remaining 1 did not show violations of maxims.